A mussel-inspired polybenzoxazine containing catechol groups. (5th December 2018) - He, Youjun; Gao, Sheng; Lu, Zaijun
Abstract: Mussel adhesive proteins (MAPs) are of an excellent adhesive property. The catechol structure (i.e., 1, 2-dihydroxybenzene) of 3, 4-dihydroxy-phenylalanine (DOPA) plays a key role in MAPs adhesion. Inspired by the MAPs adhesion, we synthesized catechol-based benzoxazine monomers (BOZ-ca) via Mannich reaction of catechol, aniline and paraformaldehyde, and then the polybenzoxazine containing catechol groups (PBOZ-ca) was obtained through the ring-opening polymerization of BOZ-ca in this work. The structure of BOZ-ca was characterized by 1 H NMR, 13 C NMR and FTIR. Interestingly, the DSC results show that the autocatalytic polymerization effect of BOZ-ca owing to the existence of phenolic hydroxyl groups decreases the polymerization temperature of BOZ-ca by ca. 80 °C compared with common benzoxazine monomers. The adhesion study results indicate that the catechol structure of PBOZ-ca increases its lap shear adhesion strength by 53% compared with common benzoxazine monomers, up to ∼2.61 MPa. The introduction of mussel-inspired structure provides a new design routine for the improvement of polybenzoxazine adhesion property. Graphical abstract: A mussel-inspired polybenzoxazine containing catechol groups is synthesized for the first time, exhibiting a higher adhesive property and lower polymerization temperature. Highlights: The mussel-inspired polybenzoxazine (BOZ-ca) containing catechol groups was synthesized for the first time. The adhesive property of PBOZ-ca increases by ca. 53% attributed to the catechol-metal coordination. The polymerization temperature of BOZ-ca decreases by ca. 80 o C owing to autocatalytic polymerization effect.